Stromal Expression of MicroRNA-21 in Advanced Colorectal Cancer Patients with Distant Metastases - Lee, Kyu Sang; Nam, Soo Kyung; Koh, Jiwon; Kim, Duck-Woo; Kang, Sung-Bum; Choe, Gheeyoung; Kim, Woo Ho; Lee, Hye Seung (Journal of pathology and translational medicine, 2016)
The aim of this study was to determine the regional heterogeneity and clinicopathological significance of microRNA-21 (miR-21) in advanced colorectal cancer (CRC) patients with distant metastasis. miR-21 expression was investigated by using locked nucleic acid- fluorescence in situ hybridization in the center and periphery of the primary cancer and in distant metastasis from 170 patients with advanced CRC. In addition, α-smooth muscle actin and desmin were evaluated to identify cancer-associated fibroblasts (CAFs) by using immunohistochemistry. The miR-21 signal was observed in the cancer stroma. The expression of miR-21 (a score of 1-4) in the center and periphery of the primary cancer and in distant metastasis was observed in specimens from 133 (78.2%), 105 (61.8%), and 91 (53.5%) patients, respectively. miR-21 expression was heterogeneous in advanced CRC. Discordance between miR-21 expression in the center of the primary cancer and either the periphery of the primary cancer or distant metastasis was 31.7% or 44.7%, respectively. miR-21 stromal expression in the periphery of the primary cancer was significantly associated with a better prognosis (p=.004). miR-21 expression was significantly associated with CAFs in the center of the primary cancer (p=.001) and distant metastases (p=.041). miR-21 expression is observed in cancer stroma related to the CAF quantity and frequently presents regional heterogeneity in CRC. Our findings indicate that the role of miR-21 in predicting prognosis may be controversial but provide a new perspective of miR-21 level measurement in cancer specimens.